Professional primary school teacher identity development: a pursuit in line with an unexpressed image. Issue 5 (19th October 2016) - Palmér, Hanna
Abstract : The results presented in this article are taken from a case study of novice primary school mathematics teachers' professional identity development from the perspective of the teachers themselves. The empirical material was collected through self-recordings, observations and interviews. The results show how the professional identity development of these novice teachers becomes a pursuit in line with their image of a primary school teacher. To develop a sense of themselves as primary school teachers they need to establish their own criteria - individual (including graduation and personal knowledge) and social (the ability to work in one school, have colleagues and have a class of their own for which they do the planning and teaching). These criteria are shown to be both a precondition for and a part of professional identity development. The novice teachers' image of what it means to be a primary school teacher directs their actions and becomes the goal of their professional identity development. Because of its high impact, student and novice teachers' image of primary school teachers ought to be made visible in both teacher education and teacher induction.